Dissecting pain processing in adolescents with Non‐Suicidal Self Injury: Could suicide risk lurk among the electrodes?. (31st May 2021) - Leone, Caterina; Galosi, Serena; Mollica, Cristina; Fortunato, Mattia; Possidente, Chiara; Milone, Valeria; Misuraca, Sofia; Berillo, Luana; Truini, Andrea; Cruccu, Giorgio; Ferrara, Mauro; Terrinoni, Arianna
Abstract: Background: Although non‐suicidal self‐injury (NSSI) disorder is highly prevalent in adolescents, its relationship with pain system function and suicidality is still controversial. The present study was designed to assess the function of the nociceptive afferent pathways and the endogenous pain modulation in adolescent patients with NSSI and to longitudinally register any suicide attempt, describe its frequency and find a possible association between suicide, neurophysiological measures and psychological measures. Methods: We enrolled 30 adolescents suffering from NSSI and 20 age‐ and gender‐matched healthy controls. Patients underwent a comprehensive psychological evaluation. Each participant underwent thermal pain thresholds of the quantitative sensory testing, laser‐evoked potential recording to study the ascending nociceptive pathway and the conditioned pain modulation testing to test the endogenous pain modulation. Results: We found that patients with NSSI had a reduced amplitude of the N2 component of laser‐evoked potentials and an abnormal conditioned pain modulation. The amplitude of the N2 was associated with suicidal risk. Conclusions: The deficit of the endogenous pain modulation likely depends on a saturation due to continuous pain solicitation. The strong association of a reduced amplitude of the N2 component with suicide suggests that it may serve as a possible biomarker in self‐harming adolescents. Significance: The present study identifies the N2 component of laser‐evoked potentials as a possible neurophysiological biomarker of suicidal risk in patients with non‐suicidal self‐injury, therefore, raising the possibility for a non‐invasive test to identify subjects at higher risk of suicide among self‐harming patients.